Noncontact tip-enhanced Raman spectroscopy for nanomaterials and biomedical applications. Issue 9 (27th August 2019) - Voylov, Dmitry N.; Bocharova, Vera; Lavrik, Nickolay V.; Vlassiouk, Ivan; Polizos, Georgios; Volodin, Alexei; Shulga, Yury M.; Kisliuk, Alexander; Thiyagarajan, Thirumagal; Miller, Duane D.; Narayanan, Ramesh; Sumpter, Bobby G.; et al.
Abstract : Demonstration of a proof of the concept and feasibility of a non-contact TERS approach promising for imaging of materials with high aspect ratio surface patterns and biomaterials. Abstract : Tip-enhanced Raman spectroscopy (TERS) has been established as one the most efficient analytical techniques for probing vibrational states with nanoscale resolution. While TERS may be a source of unique information about chemical structure and interactions, it has a limited use for materials with rough or sticky surfaces. Development of the TERS approach utilizing a non-contact scanning probe microscopy mode can significantly extend the number of applications. Here we demonstrate a proof of the concept and feasibility of a non-contact TERS approach and test it on various materials. Our experiments show that non-contact TERS can provide 10 nm spatial resolution and a Raman signal enhancement factor of 10 5, making it very promising for chemical imaging of materials with high aspect ratio surface patterns and biomaterials.